SOME ASPECTS REGARDING TRAFFIC RELATED ENVIRONMENTAL POLLUTION (PANGEEA, 2025)
The developments in the last time did show that beside positive desired effects of human economic activities, also negative undesired effects on environment and society can appear. Therefore it is impetuous necessary to analyse and evaluate these unwanted impacts of technological applications, not only on the environment, but also on the society. On a global level there is presently a huge debate related to environmental impact assessment of different economic activities and for such an assessment different tools can be used. In the present article general remarks about Life Cycle Assessment (LCA) will be presented, emphasing the emergence of this concept, as well as its usage possibilities in the context of different industrial applications. Concretely it will be mentioned that LCA has to be carried out in different stages and for different phases in the life cycle of a product. Regarding traffic engineering several transport means will be chosen and the pollutants emissions in their using phase will be assessed and compared. Conclusions regarding the traffic related environmental impacts will be drawn as well as measures to reduce these impacts will be emphasised.
Keywords: environmental impact assessment; traffic environmental pollution; life cycle assessment